2020
DOI: 10.1161/circulationaha.119.040963
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Hypermuscularization of the Transitional Segment Between Arterioles and Capillaries Protects Against Spontaneous Intracerebral Hemorrhage

Abstract: Background: Spontaneous deep intracerebral hemorrhage (ICH) is a devastating subtype of stroke without specific treatments. It has been thought that smooth muscle cell (SMC) degeneration at the site of arteriolar wall rupture may be sufficient to cause hemorrhage. However, deep ICHs are rare in some aggressive small vessel diseases that are characterized by significant arteriolar SMC degeneration. Here we hypothesized that a second cellular defect may be required for the occurrence of ICH. Methods: We studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 50 publications
6
64
0
Order By: Relevance
“…As the vascular bed ramifies from the penetrating arteriole, there is gradation in the morphology and functional characteristics of the mural cells associated with vessels. The first 3-4 branches of the vascular network (1st to 4th order) originating from the penetrating arteriole constitute a "transitional zone" (Ratelade et al, 2020). These vessels are covered by cells expressing high levels of α-smooth muscle actin (α-SMA) with ovoid cell bodies and multiple broad processes that almost completely ensheathe the underlying vessel (Grant et al, 2019;Figure 3A).…”
Section: Mural Cell Properties Transition Gradually With Increasing Bmentioning
confidence: 99%
See 1 more Smart Citation
“…As the vascular bed ramifies from the penetrating arteriole, there is gradation in the morphology and functional characteristics of the mural cells associated with vessels. The first 3-4 branches of the vascular network (1st to 4th order) originating from the penetrating arteriole constitute a "transitional zone" (Ratelade et al, 2020). These vessels are covered by cells expressing high levels of α-smooth muscle actin (α-SMA) with ovoid cell bodies and multiple broad processes that almost completely ensheathe the underlying vessel (Grant et al, 2019;Figure 3A).…”
Section: Mural Cell Properties Transition Gradually With Increasing Bmentioning
confidence: 99%
“…Both retinal and cerebral vascular cells have identical embryological origins: pericytes and SMCs derive from neuroectodermal neural crest cells and ECs derive from mesodermal hemangioblasts (Kurz, 2009;Dyer and Patterson, 2010). Structurally, the cortical and inner retinal vascular beds share a similar overall architecture, with a post-arteriolar transitional zone of 3-4 branches that are covered by contractile mural cells, leading to thin strand pericyte-covered deep capillaries (Ratelade et al, 2020). A distinction between these vascular beds is that the retinal vasculature is highly organized into two parallel plexi (Ramos et al, 2013), whereas cerebral capillaries form more elaborate three-dimensional geometries (Blinder et al, 2013).…”
Section: Box 2 | a Brief Comparison Of Retinal And Brain Vasculaturesmentioning
confidence: 99%
“…Whether further diversity is seen in other species-such as humans-is also presently unknown. A number of studies have described alterations of vascular cells in neurovascular disorders-such as neurodegenerative diseases (Alzheimer's disease and amyotrophic lateral sclerosis), intracerebral hemorrhage, and vascular malformations (Goritz et al, 2011;Winkler et al, 2011Winkler et al, , 2013Winkler et al, , 2014bWinkler et al, , 2015Winkler et al, , 2018Dias et al, 2018;Montagne et al, 2018;Sweeney et al, 2018;Ratelade et al, 2020). How vascular cell heterogeneity is altered in diseases affecting the cerebrovasculature has yet to be defined, and continued efforts are also needed to create in vitro human models which retain vascular cell diversity are needed to facilitate disease modeling.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Some have suggested that the transition from vSMCs to pericytes is discrete ( Hill et al, 2015 ; Zeisel et al, 2015 ; Vanlandewijck et al, 2018 ). Others have described a transitional cell with shared attributes between both cell types ( Hartmann et al, 2015 ; Grant et al, 2019 ; Grubb et al, 2020 ; Ratelade et al, 2020 ). Transitional cells have also been suggested in humans ( Smyth et al, 2018 ; Ratelade et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…They also identified several modifiable risk factors which may increase the risk of developing an ICH in this population, such as anticoagulant treatment, acute exercise and vaginal delivery at birth, although these factors would need to be considered on an individual basis, rather than a blanket statement for all COL4A1 patients [ 78 ]. Recently, a Col4a1 mutant mouse model has been used to mimic deep spontaneous haemorrhages which can occur in patients [ 79 ]. A novel segment (transitional segment) was identified between arterioles and capillaries which was hypermuscularised in the mutant mice, thought to play a role in the development of ICH due to subsequent increased intravascular pressure in the upstream feeding arteriole.…”
Section: Small Mammalian Modelsmentioning
confidence: 99%